Manajemen Halaqah dan Dampaknya terhadap Pembelajaran Al-Qur’an - Muhamad Riyad; Elda Rahmawati; Jamilatul Fikriah; M. Irsyadul Ibad; Najmah Ulin Ni'mah; Putri Utami; Silmi Khoridah (Edusifa: Jurnal Pendidikan Islam, 2023)
This study aims to determine the Halaqah Management and its Impact on Al-Qur'an Learningat MI PUI Barengkok, The selected sample amounted to 240 people MI PUI Barengkok in the Mafazah Islamic Boarding School Foundation. This study uses a survey method with an interview and observations analysis. The results of this study conclude that: The most relevant methods for learning the Koran for MI students are using the Iqro', Qiro'ati and Taqriran methods, habituation, example, practice, memorization and giving assignments, as well as playing, telling stories and singing. Keywords: Al Quran Learning, educational management, At Tanzil, Nubdzatul Bayan.